2021
DOI: 10.1123/jpah.2020-0305
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Physical Activity Among Emergency Medical Services Professionals

Abstract: Background: Emergency medical services (EMS) professionals demonstrate low adherence to physical activity guidelines and experience a high prevalence of obesity and incidence of injury. The authors investigate the barriers to participating in physical activity among EMS professionals. Methods: The EMS professionals employed by 15 North Carolina EMS agencies were surveyed with validated items. Multivariable logistic regression models were used to estimate the odds (odds ratio, 95% confidence interval) of not me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although no previous systematic reviews have identified barriers to physical activity among university students, some qualitative studies have shown the presence of motivational and time-related barriers as factors preventing university students from practicing physical activity [ 122 , 143 , 144 ]. Furthermore, barriers to physical activity are almost similar in reviews on different populations, for example in individuals from the Middle East and North Africa [ 145 ], pregnant women [ 146 ] and medical services professionals [ 147 ]. A recent systematic review showed that cultural values (e.g., general and gender norms) affect the practice of physical activity in specific countries (e.g., Arab countries) [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no previous systematic reviews have identified barriers to physical activity among university students, some qualitative studies have shown the presence of motivational and time-related barriers as factors preventing university students from practicing physical activity [ 122 , 143 , 144 ]. Furthermore, barriers to physical activity are almost similar in reviews on different populations, for example in individuals from the Middle East and North Africa [ 145 ], pregnant women [ 146 ] and medical services professionals [ 147 ]. A recent systematic review showed that cultural values (e.g., general and gender norms) affect the practice of physical activity in specific countries (e.g., Arab countries) [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shift workers have stated barriers to exercise as lack of opportunity, time, and already being fatigued [150]. In paramedics, other barriers to exercise have been reported as a lack of willpower or energy [152]. Generally, those with increased levels of physical activity have been found to have an increase in occupational performance due to a reduced effort exerted to work [153].…”
Section: Exercisementioning
confidence: 99%